Rhubarb polysaccharide and berberine co-assembled nanoparticles ameliorate ulcerative colitis by regulating the intestinal flora - Feng, Yifan; Wu, Chenyang; Chen, Huan; Zheng, Tingting; Ye, Hanyi; Wang, Jinrui; Zhang, Yinghua; Gao, Jia; Li, Ying; Dong, Zhengqi (Frontiers in Pharmacology, 2023)
Introduction: Inflammatory bowel disease (IBD) affects about 7 million people globally, which is a chronic inflammatory condition of the gastrointestinal tract caused by gut microbiota alterations, immune dysregulation, genetic and environmental factors. Nanoparticles (NPs) deliver an active natural compound to a site harbored by disordered microbiota, they are used to interact, target and act intentionally on microbiota. Although there is accumulating evidence indicating that berberine and polysaccharide play an important role in IBD via regulating microbiota, there is limited research that presents a complete picture of exactly how their carrier-free co-assembled nanodrug affects IBD. Methods: The study establishes the carrier-free NPs formed by berberine and rhubarb polysaccharide based on the combination theory of Rheum palmatum L. and Coptis chinensis Franch., and characterizes the NPs. The IBD treatment efficacy of NPs are evaluated via IBD efficacy index, and explore the mechanism of NPs via 16S rRNA test and immunohistochemistry including occludin and zonula occludens-1. Results: The results showed that DHP and BBR were co-assembled to nanoparticles, and the BD can effectively relieve the symptoms of UC mouse induced by DSS via regulating gut microbiota and repair the gut barrier integrity, because BD have a longer retention on the colon tissue and react with the microbiota and mucus thoroughly. Interestingly, BD can enrich more probiotic than free BBR and DHP. Discussion: This design provides a better strategy and encourages future studies on IBD treatment via regulating gut microbiota and the design of novel plant polysaccharide based carrier-free co-assembly therapies.